1998
DOI: 10.1080/002202798183620
|View full text |Cite
|
Sign up to set email alerts
|

From hackers to luddites, game players to game creators: Profiles of adolescent students using technology

Abstract: Journal of Curriculum StudiesPublication details, including instructions for authors and subscription information:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…Kafai 2002). Fewer empirical studies focused on cultural differences or equity: the only ones we found are the quasi-experimental studies by Freedman and Liu (1996) and by Royer et al (1994), and the case studies by Chisholm (1995), Maurer and Davidson (1999), DeVoogd (1998) and Upitis (1998). The study by Hativa et al (1993) is the only study on SES differences.…”
mentioning
confidence: 97%
See 3 more Smart Citations
“…Kafai 2002). Fewer empirical studies focused on cultural differences or equity: the only ones we found are the quasi-experimental studies by Freedman and Liu (1996) and by Royer et al (1994), and the case studies by Chisholm (1995), Maurer and Davidson (1999), DeVoogd (1998) and Upitis (1998). The study by Hativa et al (1993) is the only study on SES differences.…”
mentioning
confidence: 97%
“…Another way to promote self-confidence and provide support is to encourage students to help each other (Selby & Ryba 1994;Upitis 1998) or to work with expert students (Selby & Ryba 1994;DeVoogd 1998;Maurer & Davidson 1999;Gillani 2000). Especially when working with expert students it is important that the experts have been trained in the social aspects of helping others (Maurer & Davidson 1999).…”
Section: Self-confidencementioning
confidence: 99%
See 2 more Smart Citations
“…This is not to ignore or to romanticise the reality, or the image of poverty or disadvantage; rather, it is to invite a consideration of the multiple realities and the diversities that are collected together under any single label. Rena Upitis (1998) provides an excellent example of a close reading of the diversity that underlies the generalisations made possible by studies like that of Meredyth et al (1998). She studied the response of a class of Grade 7 and 8 students in a Canadian school to the introduction of four networked computers into their classroom over a 1-year period.…”
Section: Looking For Rays Of Hopementioning
confidence: 93%